Assessing the physical development of cities and extending to geomorphological prohibited areas Using LCM (Case Study: Sanandaj City) - Saeed Negahban; Hamid Ganjaeiyan; Mojdeh Feraydooni Kordestani; Ziba Cheshmeh sefidi (مخاطرات محیط طبیعی, 2019)
Considering topographic limitations of Sanandaj, the trend of spreading residential areas to hazardous areas has increased in recent years. In this regard, in the present study, the trend of the expansion of residential areas in the urban area of Sanandaj in the years 1991 to 2015 has been evaluated. The methodology is in such a way that after preparing satellite images (Landsat 5, 7, and 8) of 1991, 2000, 2007, and 2015 and preprocessing the images, land-use classification map have been prepared in four classes of residential areas, agricultural lands, gardens and rangelands for each of these years. Then, the analysis of the changes has been performed in each of the uses over the years. For this purpose, the Land Change Modeler model has been used. The results of the research indicate that each year about 1/1 km2 is added to the residential areas of the Sanandaj urban area, so that in 1991 the total urban area of Sanandaj city was 27.2 km2, while in 2015 this figure reached 54.5 km2. Then, the layer of prohibited areas in terms of geomorphologic parameters has been prepared in the ArcGIS environment. After preparing the layer of prohibited areas (Height above 2000 m, northern aspects, slopes above 30%, 1000 m of the fault zone and 200 m to riparian zone), the expansion of residential areas in the years 1991, 2000, 2007, and 2015 in prohibited areas has been evaluated. The results of the calculations indicate that, in 1991, about 7.8 km of residential areas were located in prohibited areas, which increased by 14.8 km2 in 2015. These areas are mainly located in the western part of the Sanandaj city located at Abidar highlands and in the steep areas, as well as in the eastern part of the Sanandaj area located on the riverside.